Hierarchical void structured Si/PANi/C hybrid anode material for high-performance lithium-ion batteries. (20th March 2019) - Mu, Ge; Ding, Zepeng; Mu, Daobin; Wu, Borong; Bi, Jiaying; Zhang, Ling; Yang, Hao; Wu, Hanfeng; Wu, Feng
Abstract: Silicon (Si) is regarded as the most attractive anode for high-performance lithium-ion batteries due to its high theoretical speciﬁc capacity. Unfortunately, Si experiences signiﬁcant volume changes, leading to severe capacity fading and poor cycling stability. Here, novel hierarchical void structured Si/PANi/C microspheres are designed and synthesized to tackle these problems. In this architecture, silicon nanoparticles (SiNPs) with conductive polymer conformal coating are homogeneously dispersed in a three-dimensional porous polymer framework which is partially carbonized. The void space in highly porous matrix is not only capable of accommodating volume expansion but also favorable for liquid electrolyte penetration, enabling extremely stable cycling performance and superior rate capability, along with high areal mass loading. The outside carbon layer containing nitrogen may help attain a stable solid electrolyte interphase (SEI) film. The resultant Si/PANi/C anode reaches the reversible charge capacity of 1470 mAh g −1 at 100 mA g −1 and the average capacity loss after 200 cycles is only 0.04% per cycle. Moreover, Si/PANi/C anode exhibits excellent rate performance of ∼790 mAh g −1 even at 1 A g −1 and its Coulombic efficiency increases to 99% after only 3 cycles. Remarkably, the reversible areal capacity is high with a value of 2.74 mAh cm −2 at a high mass loading of ∼1.9 mg cm −2 .